Dietary Vitamin A for Aquatic Animals - Plaipetch, Pichet; Ngamphongsai, Chansawang (Burapha Science Journal, 2026)
Vitamin A is a group of organic matters biologically active like retinol and plays important roles on vision, cell formation, embryonic development and immune system. It consists of two groups which are retinoids i.e. retinol and retinal, and carotenoids being precursors for vitamin A synthesis i.e. beta-carotene. Aquatic animals mostly deposit vitamin A in liver as ester forms of all-trans-retinol (Vitamin A1) and 3,4-dehydroretinol (Vitamin A2). Marine fish deposits only A1, but both forms for freshwater fish. Vitamin A deficient aquatic animals (Hypovitaminosis A) show a unique clinical sign of blindness or exophthalmia, while excessive dietary intake (Hypervitaminosis A) causes bone deformity, especially spinal cord. Vitamin A quantity has been preferably determined as International Unit (IU) or Retinol Equivalent (RE) accounted for 0.3 and 1 microgram of retinol, respectively. Aquatic animal feed mills mostly use synthetic retinyl acetate or palmitate as dietary vitamin A source either a single or a vitamin premix form. Currently, there have been more studies about dietary vitamin A for aquatic animals, especially at young and juvenile stages, but requirements of those groups studied cannot be clearly specified. These are because of test levels were determined with high difference, non-proportion or some high values resulted in hypervitaminosis A. However, based on previous researches and recommendations, it can be preliminarily concluded that shrimp, prawn and fish diets should contain vitamin A calculated as retinol at least 4,000 IU and not above 12,000 IU per kilogram.